Artificial Radionuclides Database in the Pacific Ocean: HAM Database - Michio Aoyama; Katsumi Hirose (The Scientific World Journal)
The database “Historical Artificial Radionuclides in the Pacific Ocean and its Marginal Seas”, or HAM database, has been created. The database includes 90Sr, 137Cs, and 239,240Pu concentration data from the seawater of the Pacific Ocean and its marginal seas with some measurements from the sea surface to the bottom. The data in the HAM database were collected from about 90 literature citations, which include published papers; annual reports by the Hydrographic Department, Maritime Safety Agency, Japan; and unpublished data provided by individuals. The data of concentrations of 90Sr, 137Cs, and 239,240Pu have been accumulating since 19571998. The present HAM database includes 7737 records for 137Cs concentration data, 3972 records for 90Sr concentration data, and 2666 records for 239,240Pu concentration data. The spatial variation of sampling stations in the HAM database is heterogeneous, namely, more than 80% of the data for each radionuclide is from the Pacific Ocean and the Sea of Japan, while a relatively small portion of data is from the South Pacific. This HAM database will allow us to use these radionuclides as significant chemical tracers for oceanographic study as well as the assessment of environmental affects of anthropogenic radionuclides for these 5 decades. Furthermore, these radionuclides can be used to verify the oceanic general circulation models in the time scale of several decades.